Gender equality issues in pre-olympic training - Maltseva, S. G.; Zakrevskaya, N. G.; Ermilova, V. V.; Putyatova, E. G. (Theory and Practice of Physical Culture, 2019)
The study analyzes the issues of gender equality in modern international sports. In 2018 the Social Technologies and Mass Communications Department of Lesgaft National State University of Physical Education, Sport and Health hosted a round table `Gender equality in the Physical Education and Sport service sector: pros and cons` with participation of the Department faculty and students. Timed to the round table discussions was a questionnaire survey of 41 people designed to complement the research project by the Department faculty.